2020
DOI: 10.1186/s13613-020-00709-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the perioperative inotropic support in grown-up congenital heart patients undergoing cardiac surgery: a propensity score adjusted analysis

Abstract: Background: Grown-up congenital heart (GUCH) patients represent a growing population with a high morbidity risk when undergoing reparative surgery. A main preoperative feature is right ventricular failure, which represents a risk factor for postoperative low cardiac output syndrome. Levosimendan has a potentially beneficial effect. This retrospective study included consecutive GUCH patients with surgeries in a tertiary cardiothoracic centre between 01-01-2013 and 01-10-2017, to test the hypothesis that the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…One study in grown-up congenital heart disease (GUCH) has been identified since 2019. In that retrospective work, Mauriat and colleagues compared outcomes in 87 patients undergoing cardiac surgery who received postoperative levosimendan (0.2 μg/kg/min/24 h) with those in 117 patients who received milrinone (0.5–1.0 μg/kg/min) [ 17 ]. Patients in either group could also receive low-dose (0.02–0.05 μg/kg/min) epinephrine or norepinephrine, as required.…”
Section: Postoperative Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study in grown-up congenital heart disease (GUCH) has been identified since 2019. In that retrospective work, Mauriat and colleagues compared outcomes in 87 patients undergoing cardiac surgery who received postoperative levosimendan (0.2 μg/kg/min/24 h) with those in 117 patients who received milrinone (0.5–1.0 μg/kg/min) [ 17 ]. Patients in either group could also receive low-dose (0.02–0.05 μg/kg/min) epinephrine or norepinephrine, as required.…”
Section: Postoperative Settingsmentioning
confidence: 99%
“…In this context, Mauriat et al [ 17 ] suggested that when levosimendan was used following surgery in GUCH patients with a high prevalence of RVF and PH, a beneficial impact on the durations of MV and ICU stay was noticed.…”
Section: Pulmonary Hypertension and Right Ventricular Dysfunctionmentioning
confidence: 99%
“…In many centers worldwide, inotropic therapy has been used routinely in managing patients undergoing cardiovascular surgery and is considered a standard of care. However, few high-quality randomized controlled trials (RCTs) have verified its efficacy, and there is no consensus on how inotropes should be used in cardiac surgery patients (1,2). Recently, an RCT has shown that the 30-day mortality and major cardiovascular complication risks were similar between the dobutamine-sparing and the dobutamine-toall strategy groups in patients with normal left ventricular ejection fraction (LVEF) (i.e., LVEF >50%) who underwent coronary artery bypass grafting (CABG) (3).…”
mentioning
confidence: 99%